Optimization of maltodextrin concentration and spray drying temperature on physicochemical characteristics of powdered edamame milk - Ali, Dego Yusa; Pramita, Hera Sisca; Widyaningsih, Tri Dewanti; Jayanti, Theresia Vania (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2024)
Peeled edamame can be processed into a product that will increase added value, including edamame milk. The perishable nature of milk requires further processing, such as drying it into powder. One of the commonly used fillers is maltodextrin because it can improve the product’s physical properties. With this treatment process, the physicochemical characteristics could be changed. Therefore, this study aimed to optimize the treatment of the physicochemical characteristics of edamame milk powder. Response Surface Methodology (RSM) with Central Composite Design (CCD) experiment with maltodextrin concentration factor (5.71%-10.00%) and spray drying temperature (160°C-215°C) was used in this study. Analysis of physicochemical characteristics carried out included water content, water activity, solubility, hygroscopicity, and color (a(-)). The results showed that treatment with the combination of 6.00% maltodextrin and 215 °C of drying temperature offer the optimum condition in producing a high-quality edamame milk powder.